Nidirana chapaensis (Bourret, 1937), one additional anuran species for the amphibian fauna of China - Yuan, Zhiyong; Liu, Xiaolong; Wang, Kai; Wang, Jian; Chen, Jinmin; Jin, Jieqiong; Wei, Pingfan; Zhou, Jiajun; Che, Jing (Zootaxa, 2019)
The China-Vietnam border region is a well-known biodiversity hotspot, harboring a striking diversity of species and endemism. However, the largest part of this region is so far understudied due to restrictions by political boundaries and difficulties in accessibility. Consequently, many species have only been reported from one side of the political boundary, despite the presence of continuous habitat on both sides. In this study, we present our discovery of the frog Nidirana chapaensis in southern Yunnan Province, China. This species was previously known only from Vietnam. All major morphometric characters of these Chinese specimens were found to match with the Vietnamese specimens. In addition, our mitochondrial phylogeny suggests that the Chinese population is monophyletic with respect to topotypic Nidirana chapaensis, with uncorrected pairwise distances of 0.2% at the COI gene fragment analyzed. Therefore, we report Nidirana chapaensis as a new member of amphibian fauna of China, describe the morphological variation of the Chinese population, and provide additional natural history data of this species based on our observation from China.